A reduced modal subspace approach for damped stochastic dynamic systems. (December 2021) - Kasinos, S.; Palmeri, A.; Lombardo, M.; Adhikari, S.
Highlights: A method for characterising system uncertainty in the modal space of linear systems. It reduces the number of uncertain parameters and the size of the dynamic problem. Model parameters can be calibrated based on information from the geometrical space. A high-order perturbation technique for the multi-fidelity response quantification. Demonstrated on the dynamic analysis of a multi-storey steel frame and a bridge. Abstract: A novel method for characterising and propagating system uncertainty in structures subjected to dynamic actions is proposed, whereby modal shapes, frequencies and damping ratios constitute the random quantities. The latter, defined in the modal subspace rather than the full geometrical space, reduce the number of the random variables and the size of the dynamic problem. A numerical procedure is presented for their identification by calibrating their probabilistic definition in line with the geometrical space. A high-order perturbation technique is proposed for the multi-fidelity response quantification by means of an ad hoc extension of the conventional perturbation method. The approach involves a set of auxiliary deterministic differential equations to be adaptively solved with the piecewise exact method, and moment-cumulant relationships are employed to approximate high-order moments. Finally, a polynomial chaos expansion approach is adopted to complement the second-moment analysis for spectral quantification with the modal subspace reduction. Demonstrated on a multi-storey steel frame with semi-rigid connections and a simply supported bridge subjected to a moving load, the proposed variants exhibit improved performance with respect to the conventional second-order and improved perturbation, as well as increased flexibility, enabling the analyst to decide, on-demand, the level of fidelity, balancing accuracy and computational effort.